2017
DOI: 10.1158/1538-7445.epso16-b46
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B46: Surface chemistry governs cellular tropism of nanoparticles in the brain

Abstract: Purpose: Nanoparticles (NPs) carry important promises for the treatment of neurological diseases, such as glioblastoma multiform (GBM) and Parkinson's disease. Several methods have been developed to achieve higher NP concentrations in the brain, including local infusions using convection enhanced delivery (CED), focused ultrasound, and the use of surface targeting moieties specifically designed to increase the passage across the blood brain barrier (BBB). However, even when sufficient NP amounts are delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…S5B). These findings confirm the preferential cellular uptake of sgPNA/BNP into glioma cells, which is consistent with our previous studies (26,52).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…S5B). These findings confirm the preferential cellular uptake of sgPNA/BNP into glioma cells, which is consistent with our previous studies (26,52).…”
supporting
confidence: 93%
“…NPs formed from PLA-HPG-CHO are bioadhesive nanoparticles, or BNPs (48)(49)(50)(51). We have shown that-compared with several other NPs of similar composition-these BNPs lead to the highest levels of uptake into intracranial tumor cells after CED (52) and they can be loaded with PNAs, which are slowly released after CED in the brain (53). In this work, we loaded the PLA-HPG-CHO BNPs with two sgPNAs-one binding to miR-10b and another binding to miR-21-to test the hypothesis that simultaneous delivery of two anti-miRs in glioma cells can regulate unique molecular pathways leading to improved survival.…”
Section: Introductionmentioning
confidence: 93%
“…The period of rapid elimination of VE822 (half-life of 2 hr, more rapid than the clearance rate of free drug) is due to elimination of NPs containing VE822, whereas the sustained levels are the result of a competition between slow VE822 release from the remaining intracellular NPs, elimination of free VE822, and slow elimination/degradation of the remaining NPs. We still have work to do in determining the relative contributions of these multiple routes for elimination in the tumor microenvironment, but recent experiments suggest that some of these mechanisms can be manipulated by changing properties of the NP, such as surface chemistry (5961). Still, even with our present formulation, NP-VE822 was able to maintain intracranial drug levels above the IC50 of VE822 (0.125uM) for at least 10 d after administration.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we selected a molecule with minimal effect on NHEJ in an effort to maximize the therapeutic ratio. Additionally, the passive targeting of NP-formulations that allows enhanced uptake in mitotically active cells such as tumor cells seems to supplement this selective tumor targeting and even further widen the gap of relative toxicity between healthy and tumor cells (59). …”
Section: Discussionmentioning
confidence: 99%
“…PLA-HPG NPs loaded with the DiA dye (0.2% w/w) at a final concentration of 100 mg/mL in PLA-HPG were prepared by the emulsion-evaporation technique as previously described [17]. Brain penetrating PLGA NPs loaded with Nile Red (0.2% w/w) at a final concentration of 100 mg/mL in PLGA were prepared by the emulsion-evaporation technique followed by centrifugation steps to recover small particles, as previously described [18].…”
Section: Methodsmentioning
confidence: 99%